2021
DOI: 10.48550/arxiv.2105.11631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical trapping of nanoparticles in superfluid helium

Yosuke Minowa,
Xi Geng,
Keisuke Kokado
et al.

Abstract: Optical tweezers, the three-dimensional confinement of a nanoparticle by a strongly focused beam of light, have been widely employed in investigating biomaterial nanomechanics, nanoscopic fluid properties, and ultrasensitive detections in various environments such as inside living cells, at gigapascal pressure, and under high vacuum. However, the cryogenic operation of solidstate-particle optical tweezers is poorly understood. In this study, we demonstrate the optical trapping of metallic and dielectric nanopa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Laser ablation, or sputtering, is a unique in-situ preparation method to produce atoms, ions, and nano/microparticles in various environments; it is also applicable to superfluid 4 He. Laser ablation in superfluid 4 He has been used for precision spectroscopy[1-3], tracer injection [20], nano/micro structure formation [5,6], and optical manipulation/trapping [21,22]. In this study, we observed the silicon nanoparticledecorated, suspended quantised vortices, and identified the vortex reconnection events [13], the dynamics of which were found to be consistent with the results of dimensional analysis the simple vortex filament model (VFM) calculations.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Laser ablation, or sputtering, is a unique in-situ preparation method to produce atoms, ions, and nano/microparticles in various environments; it is also applicable to superfluid 4 He. Laser ablation in superfluid 4 He has been used for precision spectroscopy[1-3], tracer injection [20], nano/micro structure formation [5,6], and optical manipulation/trapping [21,22]. In this study, we observed the silicon nanoparticledecorated, suspended quantised vortices, and identified the vortex reconnection events [13], the dynamics of which were found to be consistent with the results of dimensional analysis the simple vortex filament model (VFM) calculations.…”
Section: Introductionsupporting
confidence: 64%
“…This finding clearly supports the hypothesis that the quantised vortex plays a major role in the formation of the semiconducting or metallic nanowires in superfluid 4 He [5,12,16,18,[25][26][27], although the intermediate process needs to be further studied. The laser ablation method can inject various nanoparticles, ranging from semiconductors [21] to metals [5,22], into superfluid 4 He.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation